Habitat conservation enhances the resilience of the lizard Liolaemus cuyumhue to high summer temperatures - María Victoria Brizio; Facundo Cabezas-Cartes; Luciano Javier Avila; Jorgelina Mariela Boretto (Scientific Reports)
Abstract Habitat degradation from human activities affects essential microhabitats, threatening ecological processes like foraging, mating, locomotion, predator evasion, and competition among reptiles. We assessed how microhabitat selection and body temperature of the endangered lizard Liolaemus cuyumhue respond to differences in vegetation composition and thermal conditions between a disturbed site and an undisturbed site impacted by oil and gas activities in Argentina. During five expeditions between September 2022 and March 2023, we searched for L. cuyumhue and collected data on body temperature, substrate and air temperatures, body mass, snout-vent length, sex, and habitat characteristics. We also measured operative temperatures and assessed vegetation cover and microhabitat availability at each site. Our results showed significant differences in microhabitat characteristics and selection between sites. The undisturbed site had higher vegetation and lower operative temperatures, while the disturbed site had higher temperatures and lower vegetation, especially in summer. Lizards at the disturbed site showed higher body temperatures, suggesting stressful thermal conditions, and preferred microhabitats with lower bare ground cover. Capturing lizards in the disturbed site required more effort than in the undisturbed site. This study emphasizes the impact of habitat disturbance on the thermal environment and behavior of L. cuyumhue. Conservation efforts should prioritize maintaining and restoring vegetation to support the species’ thermoregulation needs, especially under global warming.